EKSISTENSI AKTA JUAL BELI HAK MILIK ATAS TANAH YANG DIBUAT PEJABAT PEMBUAT AKTA TANAH CAMAT DIKECAMATAN MENDOYO KABUPATEN JEMBRANA - Suta Eni, Nyoman; Agung, I Gusti Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 06, Oktober 2014)
The existence of the Land is very important because it is a place where people do alltheir activities. With the increasing population and limited land area, the state strictlyregulates the land, the rights attached to its owner, as well as the status of land ownershiptransfer procedures such. In regard to the role of Land deed Official are given the duty andauthority to make the deed as proof of ownership and transfer of copyright law subject to aground. Formulation of the problem that arises is about the legal status of the Deed of Salemade by the district head as Land deed Official in connection with the sale and purchase ofthe land and how the existence of the Deed Law published Land deed Official with Land deedOfficial districts in buying and selling land. To discuss this empirical research methods used.The concluded that the status of the Law of the Land Sale and Purchase Agreements issued byLand deed Official sub regency chief have any legal force so as a result of the Law on LandSale and Purchase Agreements made by the district head as Land deed Official , had no effecton the process of making the certificate Land Rights held at the office of the Agency NationalLand.
Keywords: Deed of Sale of Ownership Rights to Land , Head , Land Deed Official